Bioecological, Properties And Agrotechnology Of Growing Of The Medicinal Plant Capsella Bursa-Pastoris (L.) In The Conditions Of Karakalpokistan (Texas Journal of Agriculture and Biological Sciences, 2025)
The article analyzes ethnobotanical data on the use of natural medicinal plants in Karakalpakstan. Currently, there are 63 families of medicinal plants, 444 species belonging to 240 genera, which grow in natural conditions in the region, which is 40% of the total flora. The use of herbs identified in the process of interviews with doctors in the form of a questionnaire on the use of these medicinal plants in folk medicine. The flora of Uzbekistan consists about 4 500 species of vascular plants due to it’s biogeographically features, which make a center of medicinal plant diversity (sharply continental climate, availability sultry deserts and high mountains, abundance of endemic flora). About 600 species of medicinal plants has been used in traditional medicine, but according to last research we can confirm that in Uzbekistan are growing 1154 species, which are supposed to be medicinal.